Digital Padlet and Livewoksheet Learning Media Creation Education for PAUD Teachers in IGABA Berau Regency - Cahyani, Esta Rahma; Oktafera, Ria; Latifah, Annazmil Fayroz; Sakinah, Fitriah; Sabariah, Sabariah; Ruslianti, Ruslianti; Sianturi, Lilis Dewi Sartika (Jurnal Pengabdian Masyarakat Formosa, 2023)
The Padlet and Liveworksheet Digital Learning Media Creation Training is a Community Service (PKM) activity which aims to increase knowledge, skills and strategies for PAUD Teachers in IGABA Berau Regency in using digital media for learning preparation and asesmen in the implementation of the Merdeka Curriculum. The implementation of PKM begins with an analysis of the situation and potential, namely the uneven competency of teachers in using digital learning media, then looking for alternative solutions to the problem by providing training, then selecting the digital learning media needed by PAUD teachers, and carrying out training. The impact of this activity increases teacher motivation to develop themselves, increases teacher understanding and competence in using digital learning media and is an effort to fulfill students' rights to receive quality learning.